Hubungan antara Kadar HbA1c dan Derajat Retinopati Pasien Diabetes Melitus Tipe 2 di Rumah Sakit Mata Cicendo Bandung - Farhani, Fathia; Wahab, Zulfachmi; Tursinawati, Yanuarita (Jurnal Kesehatan Andalas, 2023)
Diabetic retinopathy is the common complication of T2DM, which leads to vision loss. The severity of retinopathy can be affected by HbA1c levels. Controlling the glycemic such as HbA1c, may prevent the severity of diabetic retinopathy. Objective: To identified the association between HbA1c levels and severity of retinopathy in Type 2 DM patients at Cicendo Eye Hospital, Bandung. Methods: This research was an analytic observational study and cross-sectional approach. Samples were taken using purposive sampling and consisted of 70 people. The secondary data were from the outpatient's medical records at the Cicendo Eye Hospital in Bandung for the period September-October 2022. The Chi-square test was used for data analysis. Results: According to HbA1c levels, the uncontrolled HbA1C levels were found in 52 patients (74,3%) and the controlled were found in 18 patients (25,7%). Most of them were diagnosed with PDR were found 62% and the rest of it were diagnosed with NPDR. A significant association is found between HbA1c levels and the degree of diabetic retinopathy with p-value = 0.018 (p <0.05). Conclusion: HbA1c levels in Type 2 Diabetes Mellitus patients have a significant association with the severity of diabetic retinopathy, which can be used as a parameter for controlling diabetes complications, particularly retinopathy.Keywords: diabetic retinopathy, T2DM, HbA1c, glycemic control